2020
DOI: 10.1108/yc-06-2020-1161
|View full text |Cite
|
Sign up to set email alerts
|

Young adolescents’ experiences and views on eating and food

Abstract: Purpose Poor eating habits established during adolescence are likely to lead to negative long-term health consequences. The childhood obesity epidemic is a growing public health concern, largely attributed to obesogenic environments. This study aims to explore the multiple factors contributing positively or negatively to young consumers’ attitudes towards their food consumption. Design/methodology/approach In total, 42 11- to 13-years-old (24 men and 18 women) from three secondary schools in Wales participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 60 publications
0
26
0
Order By: Relevance
“…A total of 4375 records was excluded based on title and abstract (of which 9 based on non‐English language) and we screened the full‐text of 43 records for eligibility. Nineteen records were excluded after the full‐text screening, as they did not research children, 42 , 43 , 44 did not research marketing exposure, 45 , 46 , 47 did not research HFSS products, 48 , 49 , 50 only described the influence of social media or advergaming in combination with television or other online media, 51 , 52 , 53 , 54 , 55 or because the record was not a peer‐reviewed scientific article presenting primary research. 56 , 57 , 58 , 59 , 60 The references of the included studies were checked for eligibility, from which two additional studies were identified and included.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 4375 records was excluded based on title and abstract (of which 9 based on non‐English language) and we screened the full‐text of 43 records for eligibility. Nineteen records were excluded after the full‐text screening, as they did not research children, 42 , 43 , 44 did not research marketing exposure, 45 , 46 , 47 did not research HFSS products, 48 , 49 , 50 only described the influence of social media or advergaming in combination with television or other online media, 51 , 52 , 53 , 54 , 55 or because the record was not a peer‐reviewed scientific article presenting primary research. 56 , 57 , 58 , 59 , 60 The references of the included studies were checked for eligibility, from which two additional studies were identified and included.…”
Section: Resultsmentioning
confidence: 99%
“…The challenge, or perhaps the opportunity, is that intrinsic value and emotio-cultural value are more likely to be developed with the availability of time. The lack of time people in the UK have to commit to food, whether that be eating a healthy diet, sharing food with others, expanding their knowledge, time to shop, or even wishing to spend their time in other ways challenges the development of alter-values based food networks and the reimagining of food beyond its exchange value [119][120][121]. AFNs allow for new places within the food environment to develop, with different values associated with them, both financial and non-financial.…”
Section: Discussionmentioning
confidence: 99%
“…Next, Parents influence on adolescent highlighted that; parents are the most effective source in encouraging adolescents to eat healthy food (Chan et al, 2010), Children are vulnerable through the posts in social media by their parents (Fox and Hoy, 2019), parents are more influential than peer group in fast food consumption (Gilmour et al, 2020;Rydell et al, 2008).…”
Section: Analysis Of Areas Of Adolescent Consumer Vulnerabilitymentioning
confidence: 99%
“…Additionally, it is evident that junk food marketing appeals (Harris et al, 2020;Elliot, 2017;Beaudon, 2014) However, desired research findings do not exist to figure out the role of socio-demographic variables, and how those variables may alter the relationship between socialization agents and adolescent consumer vulnerability (Shin et al, 2019;Davis, 2013, Lueg et al, 2006). Meanwhile, the existing authors highlighted the importance of studying several socio-economic variables; Age cohorts (Lapierre et al, 2017;Lenka and Vandana,2015;Ozdogan and Atlantis,2010;Chan et al, 2010) Gender (McCoy et al 2017; Ozdogan and Atlantis, 2010), Family status (Gilmour et al, 2020;Fox and Hoy, 2019;Shin et al, 2019;Lueg et al, 2006) in upcoming researches.…”
Section: Existing Research Gaps and Suggestions For Future Researchesmentioning
confidence: 99%